2021
DOI: 10.2186/jpr.jpr_d_20_00240
|View full text |Cite
|
Sign up to set email alerts
|

Trueness and fitting accuracy of maxillary 3D printed complete dentures

Abstract: Purpose: The trueness and fitting accuracy of complete dentures (CDs) manufactured digitally from wax dentures have not been investigated yet. This study evaluated the trueness and fitting accuracy of maxillary CDs manufactured using computer-aided design technology. Methods: CD bases were manufactured from fully edentulous maxillary casts using a milling machine and three three-dimensional (3D) printers (two stereolithography apparatus (SLA) and one digital light processing (DLP)). 3D printing was performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Furthermore, as the light from the SLA printer penetrates the resin monomer to a certain depth, the light source intensity is defined by the type and color of the resin material, which affects accuracy [13]. Previous comparative studies have investigated the accuracy of relatively highly accurate denture bases fabricated using different resin materials and printing protocols [9,11,16,17,[19][20][21]. The contradictory results of these studies and the present study may be attributed to the use of the printer, resin material, denture design, orientation, layer thickness, post-polymerization, and support structure configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as the light from the SLA printer penetrates the resin monomer to a certain depth, the light source intensity is defined by the type and color of the resin material, which affects accuracy [13]. Previous comparative studies have investigated the accuracy of relatively highly accurate denture bases fabricated using different resin materials and printing protocols [9,11,16,17,[19][20][21]. The contradictory results of these studies and the present study may be attributed to the use of the printer, resin material, denture design, orientation, layer thickness, post-polymerization, and support structure configurations.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, the application of such procedures in production processes is an exciting avenue [6]. Various factors can influence the denture accuracy during the AM printing process, including the type of AM technology and manufacturer [7][8][9][10][11], type of material, layer thickness [7,[11][12][13][14], depth of cure [7,12,15], build orientation (build direction and angle) [9,11,[16][17][18][19], platform position [16], post-processing procedure [7,15,16,20,21], and amount and configuration of the support structures [16,21,22]. Stereolithography (SLA) is an AM technique that selectively cures liquid photopolymers in vats via light-activated polymerization [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies evaluated denture bases manufactured by CAD/CAM and conventional techniques, these studies used surface matching software focused on accuracy of the denture base. The findings revealed that higher deformation was in the conventionally made dentures, whilst less deformation was associated with rapid prototyped dentures (11,(18)(19)(20) .…”
Section: Retentionmentioning
confidence: 96%
“…30,31 Yoshidomea studied the trueness and fitting accuracy in conventional dentures, CAD/CAM dentures and two systems of 3D printed dentures (stereolithography and digital light processing). 32 He concluded that the milled dentures showed better trueness and fitting accuracy compared with 3D printed and conventional dentures. Moreover, 3D printed dentures showed similar trueness and fitting to conventional dentures.…”
Section: Trueness and Fitting Accuracymentioning
confidence: 99%